2013
DOI: 10.1021/jp400565m
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for the Immobilization of Bacteriophages on Gold Surfaces Monitored by Surface Plasmon Resonance and Surface Morphology

Abstract: The use of bacteriophages as recognition elements for biosensing techniques has recently provoked much interest. Surface plasmon resonance, scanning electron microscopy, and atomic force microscopy were used for the real-time monitoring of the attachment of methicillin-resistant Staphylococcus aureus (MRSA) bacteriophages to gold using several immobilization methods. The MRSA bacterial capture efficiency of phage-functionalized surfaces was studied. We found that whereas the physisorption of phages to gold sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 14 publications
(35 reference statements)
1
53
0
Order By: Relevance
“…Based on these results, our combination of 11-MUA and EDC/NHS provided a better phage density (5.5 ± 0.1 phages/µm 2 ). In addition, our results also partially agreed with Tawil et al's [34] study, which found that the combination of 11-MUA and EDC/ NHS enhanced the phage density (data were not provided) and finally improved the binding of the target, Staphylococcus aureus, onto the sensor surface. Therefore, the combination of 11-MUA and EDC/NHS could be an effective method for the immobilization of B. cereus-specific phages.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Based on these results, our combination of 11-MUA and EDC/NHS provided a better phage density (5.5 ± 0.1 phages/µm 2 ). In addition, our results also partially agreed with Tawil et al's [34] study, which found that the combination of 11-MUA and EDC/ NHS enhanced the phage density (data were not provided) and finally improved the binding of the target, Staphylococcus aureus, onto the sensor surface. Therefore, the combination of 11-MUA and EDC/NHS could be an effective method for the immobilization of B. cereus-specific phages.…”
Section: Resultssupporting
confidence: 90%
“…Although the direct adsorption method is popular and has been commonly used for the immobilization of filamentous E2 phage owing to its simplicity and practicality, the relatively weak bindings and poor orientation were problematic on the sensor surface [26,30]. To overcome the limitations of the direct adsorption method, a combination of 11-MUA and EDC/NHS was introduced owing to its recognition as the most efficient immobilization method for phages [34]. In addition, the concentration of the lytic, tailed phage is an important factor not only to allow the appropriate phage orientation with certain distances but also to avoid or minimize phage aggregation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also this methodology suffers due to variability and bacteriophage detachment in turn to the physico-chemical fluctuations in the analyte medium. Covalent bonding of phages offered a more stronger attachment and is not at risk to easy detachment of phages [53,54]. Proper chemical studies can make easy selection of suitable substrate and then potential application.…”
Section: Immobilization By Physisorption Electrostatic Bindings and mentioning
confidence: 99%
“…Several studies have been reported regarding immobilization of phages on various substrates such as glass, gold, polytetrafluoroethylene, polyethylene, paper, cellulose, etc. (Anany et al 2011;Pearson et al, 2013;Singh et al, 2009;Yang et al, 2013;Tawil et al, 2013). Also, the number of phages immobilized on a surface can be increased using nanoparticles as it is a well known-fact that as the size of a particle decreases, the ratio of the surface area to the volume of the particle increases, causing a large number of the entities to reside on the surface (Bashar et al, 2013).…”
Section: Academic Publishersmentioning
confidence: 99%